Suriname : Request for Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Suriname. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper mainly discusses the IMF-supported program aimed at restoring macroeconomic stability and confidence in Suriname's economy. The proposed 24-month Stand-By Arrangementa(265 percent of quota, or SDR 342 million) aims to support Suriname's adjustment to the fall in commodity export prices and restore external and fiscal sustainability. It foresees an improvement of the fiscal balance by 7.4 percent of GDP, which would reverse the rise in the government debt-to-GDP ratio; restore foreign reserves to adequate levels-four months of imports; and reflect a monetary policy stance calibrated to reduce inflation to single digits. It also strengthens the foundations for private-sector growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet